Exploring the Themes in Vishal Bhardwaj's Trilogy: A Deeper Look at Shakespearean Influences - Jaffar, Nosheen; Mohammed, Lubna Ali; Saleem, Muhammad (Pakistan Languages and Humanities Review, 2024)
This study aims to dissect how Bhardwaj's trilogy (Maqbool, Omkara, and Haider) reflects Shakespearean themes while weaving in contemporary Indian social issues. Vishal Bhardwaj's celebrated trilogy reimagines Shakespeare's tragedies in modern India. This study delves into how these adaptations retain core themes while reflecting social issues like caste, corruption, and political conflict.This study is qualitative in nature. Textual and Cinematic analysis have been conducted and data has been taken from primary and secondary sources. Bhardwaj's films transplant Shakespeare's tragedies into the underbelly of contemporary India (mafia, politics, and insurgency). Shakespearean themes like ambition, betrayal, and revenge form the core, but they're colored by social hierarchy, corruption, and political turmoil. The study reveals a profound integration of Shakespearean themes into Vishal Bhardwaj's trilogy, transcending cultural boundaries to resonate deeply within the Indian context. Through nuanced exploration, it uncovers themes of power dynamics, betrayal, and human complexity, showcasing how Bhardwaj skillfully adapts these timeless elements to reflect contemporary societal issues. The results underscore the enduring relevance and universal appeal of Shakespeare's works, as interpreted through the lens of Indian cinema.